Polymorphism of RAPD and ISSR markers in grain amaranth species - S. V. Lymanska; L. A. Miroshnichenko; T. I. Goptsiy; O. S. Korneeva (Вавиловский журнал генетики и селекции)
Different molecular genetic markers are effectively used in agricultural genetic selection programs. Genetic markers can be used in commercial breeds certification performance, fast and reliable genotype identification, genetic maps creation, genetics, phylogeny and plant systematic studies, which can accelerate selection, provide effective study and culture genofond maintenance. Amaranth, in this regard, has not been studied well, there is not enough data to effectively perform amaranth marker selection or for the certification of new and existing varieties; there are inaccuracies in the systematization of the crop. Important are the questions about the origin of grain amaranth species and the processes of their evolutionary formation. Amaranth is a pseudo-cereal with a millennia-long history, it has been actively cultivated in many countries around the world in recent decades. A high level of alterability and the formation of a huge number of spontaneous hybrids in natural populations of amaranth significantly complicate the identification of individual genotypes and entire taxonomic units of Amaranthus L. Due to the lack of research and depending on the environmental conditions, the morphological markers of amaranth are not able to provide sufficient genomic information to the breeder; thus it is necessary to search for reliable genetic markers that allow the genetic diversity of the Amaranthus L. species to be studied and effectively maintained. This research includes grain amaranth species DNA polymorphism analysis. Using RAPD and ISSR technologies, 203 loci have been identified, of which 173 appear to be polymorphic, 30 monomorphic (found in all genotypes analyzed) and 13 unique (found only in one genotype). Unique and monomorphic DNA loci can be used as specific genetic markers, in particular, for the certification of breeds, which is especially important for the identification of plant material and plant genetic variability monitoring. A high level of DNA polymorphism was revealed (about 85 %), a genetic relationship between grain amaranth species established, their monophyletic origin theory verified. A. mantegazzianus Passer. was proved to be an A. caudatus L. subspecies.